Medieval cemetery in Słaboszewo near Mogilno: the analysis of mortality - Piontek, Janusz (Anthropological Review, 1977)
The purpose of the present paper is to analyse mortality structure of the skeletal population originating from medieval cemetery (XIV-XVII century) excavated at Słaboszewo near Mogilno (NW segment of Central Poland). The cemetery had been incessantly used by a human group inhabiting 6 settlements dispersed on an area of 39 square kilometers and consisted of about 290 persons in the year 1350 and of 471 persons in 1775. On the cemetery there were excavated 454 burial pits and 56 ossuaries, from these last into analysis were included remains of children. Analysis of mortality structure was performed by computing life table with assumed stationary population state (tab. 1) and with stable population model at natural increase +4 per thousand per year. The rate of natural increase was assumed arbitrarily on grounds of results obtained by E. Vielrose and S. Borowski during their historical-demographic studies. Possibility of natural selection operation through differential mortality was estimated with use of three synthetizing measures of population's biological state: selection index — Im, Biological State Index — Ibs and potential gross reproductive rate — Rpot.Distribution of deaths by age in the examined population, when all individuals are considered, does not show peak of mortality in any age class, except for the first one — 0-1 years. Death frequency of newborns amounting to 10.4% seems to be too low in comparison with mortality structure of adults if we do not assume existence of birth control in the population. There are differences in distributions of deaths in adult males and females (tab. 1). Because of these differences life expectancy at birth (e00) is higher in males of 2.7 years and e020, of 2.9 years. Both differences are statistically significant when double standard error of life expectancy value is taken as a criterion of significance. Parameters of life table computed with assumed stable population state at rate of natural increase +4 per thousand per year do not differ significantly from those computed for assumed stationary population state.The value of life expectancy at birth computed for the cemetery is relatively high in comparison to that for XIX century population from the same region which demographic description was made on ground of parish registers data. Hence it is assumed that high e00 value for the cemetery is an artifact resulting from underrepresentation of newborns and young children in the skeletal sample. The main reason for this underrepresentation seems to be a lack of preservation of all children's graves in the cemetery. In this situation it has been decided to estimate actual death frequency in age group 0-15 years on the basis of differential mortality during reproductive period of life and “archetype of fertility”. Estimated frequency of deaths in ages 0 through 15 amounts to 52.9% in comparison to 39.3% found in excavated material. The difference between these two values — 13.6% — was partitioned into subadult age classes accordingly to subadult mortality structure. In the Table 3 values dx'' note death frequencies in successive age categories, with estimated subadult morality and assumption of stable population state with positive natural increase (+ 4‰).Mortality structure of the medieval population of Słaboszewo is the same as in majority of historical populations from the same region. With high mortality of newborns and children, deaths of adults are dispersed evenly in all age classes, in comparison with XIX century population there is lower frequency of senile deaths and higher proportion of deaths previous to the age of 30 years, Measures of the biological state (tab. 4) suggest that with found mortality structure in the population opportunity for natural selection operation through differential mortality was high.In the paper it was also attempted to demonstrate that application of all possible and availabe methods together with observation of various aspects of mortality structure, results of investigations into fertility structure and capacity for natural increase gives opportunity to ameliorate considerably informational value of paleodemographic analysis. In the studies of this sort it is necessary, along with application od good methods of data elaboration, to introduce model approaches and synthetizing measures for estimation of population's biological state.